Mesophilic Anaerobic Co-Digestion of Fruit and Vegetable Waste and Domestic Primary Sewage Sludge: Performance and Kinetic - Seswoya, Roslinda (International Journal of Integrated Engineering, 2019)
Wastes such as fruit and vegetable waste and sewage sludge are not easy to be manage because of their chemical and physical properties. These waste also high putrescible. Recent years, landfill disposal is no longer a sustainable way for waste management as the area of landfill has become more limited. Therefore, new approach such anaerobic digestion should be considered for these wastes. However, the mono-digestion has a drawback, including lesser methane yield due to the substrate characteristics. To overcome this problem, the co-digestion is introduced, in which two or more substrate feed to the digester concurrently. This study aims to evaluate the performance and the kinetics from the co-digestion of fruit and vegetable waste with domestic primary sewage sludge. In this study, the bio-methane potential assay (BMP) at batch mode is conducted. The BMP assay is carried out at the inoculum to substrate (I/S) ratio of 2.0 at 37oC. The kinetics analysis was included using Modified Gompertz Modelling. The characteristics study showed that the complex organic compounds existed in form of particulate mostly. The methane production was stopped at day 12 resulted in the ultimate methane yield of 1149.50 mLCH4/gVS. In addition, the methane kinetics parameter observed from laboratory work slightly   different from what was observed from the modelling.